2010
DOI: 10.1088/0957-4484/21/14/145603
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule bundle formation driven by ATP: the effect of concentrations of kinesin, streptavidin and microtubules

Abstract: Recently, a method was established for the formation of microtubule (MT) assemblies by an active self-organization (AcSO) process, in which MTs were crosslinked during sliding motion on a kinesin-coated surface, and this was coupled with adenosine triphosphate (ATP) hydrolysis. Streptavidin (ST) was the glue used to crosslink biotin-labeled MTs. Although most of the MT assemblies were in the bundle form, they varied in size, shape and motility, depending on the initial conditions used. In this paper, we system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
(34 reference statements)
2
35
2
Order By: Relevance
“…Our average loop radius is about 1 µm, whereas spools are typically larger 2-10 µm in radius (Hess et al 2005, Kawamura et al 2008, Liu et al 2008. Fourth, previous groups have found that spools form and rotate in a counter-clockwise direction (Kawamura et al 2010a). We find there is no preference for a specific rotation direction of our loops (supplemental figure 1 available at stacks.iop.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Our average loop radius is about 1 µm, whereas spools are typically larger 2-10 µm in radius (Hess et al 2005, Kawamura et al 2008, Liu et al 2008. Fourth, previous groups have found that spools form and rotate in a counter-clockwise direction (Kawamura et al 2010a). We find there is no preference for a specific rotation direction of our loops (supplemental figure 1 available at stacks.iop.…”
Section: Resultsmentioning
confidence: 49%
“…Previous studies have observed the formation of microtubule 'spools' created using microtubule-gliding assays and cross-linked microtubules that bundle together (Liu et al 2008, Hess et al 2005, Kawamura et al 2008, 2010b, 2010a. The likely mechanism of spool formation appears to be pinning of a bundle on a dead kinesin in the gliding chamber that allows for high curvature and then cross-linking of the bundle to itself (Hess et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…MT concentration was fixed at 1000 nM and the crosslinker ratio (St/Bt) was kept at 1/3.8 for allowing MTs to preferentially form ring-shaped assembly by AcSO. 10,11 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Depending on the experimental conditions such as MT concentration and crosslinker ratio (St/Bt), AcSO of MTs provides bundle-, network-, and ring-shaped assemblies which generate translational, amoeboid and rotational motion respectively. 10,11 Among them, the ring-shaped assembly have been attracting considerable attention and appears to be a promising candidate for application in nanotechnology as this non-equilibrium structure is capable of storing a huge amount of bending energy 8 and can provide continuous work without changing the position of the mass center. [12][13][14][15][16] Therefore, it is important to understand how different factors affect the formation and properties of ring-shaped MT assemblies such as rotational direction, thickness (subtraction of inner diameter from outer diameter), size etc..…”
Section: Introductionmentioning
confidence: 99%
“…(Fig. 34.2b) [21,22]. Bundles, networks, and ring-shaped microtubule assemblies offer diverse functions, quite different from that of a single microtubule filament, as reflected through translational, amoeboid and rotational motion, respectively ( Fig.…”
Section: Active Self-organization Of Biomolecular Motorsmentioning
confidence: 99%